2006
DOI: 10.1159/000092746
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Gallbladder Function and <i>Helicobacter pylori</i> Infection to Gastric Mucosa Inflammation in Patients with Symptomatic Cholecystolithiasis

Abstract: Background: Inflammatory alterations of the gastric mucosa are commonly caused by Helicobacter pylori (Hp) infection in patients with symptomatic gallstone disease. However, the additional pathogenetic role of an impaired gallbladder function leading to an increased alkaline duodenogastric reflux is controversially discussed. Aim: To investigate the relation of gallbladder function and Hp infection to gastric mucosa inflammation in patients with symptomatic gallstones prior to cholecystectomy. Patients: Sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
0
8
1
1
Order By: Relevance
“…While Silva et al [11] reported earlier that even though their findings pointed toward a real association between H. pylori infection and cholecystitis, they did not rule out the possibility that H. pylori colonized a previously damaged epithelium. Stathopoulos et al [15] have investigated the relation of gallbladder function and H. pylori infection to gastric mucosa inflammation in patients with symptomatic gallstones prior to cholecystectomy and reported that the gallbladder function is not related to the degree of gastritis. So it appears that several important factors and requirements have to be met in order to establish a definitive association between the presence of H. pylori and biliary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…While Silva et al [11] reported earlier that even though their findings pointed toward a real association between H. pylori infection and cholecystitis, they did not rule out the possibility that H. pylori colonized a previously damaged epithelium. Stathopoulos et al [15] have investigated the relation of gallbladder function and H. pylori infection to gastric mucosa inflammation in patients with symptomatic gallstones prior to cholecystectomy and reported that the gallbladder function is not related to the degree of gastritis. So it appears that several important factors and requirements have to be met in order to establish a definitive association between the presence of H. pylori and biliary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, Griniatsos et al [ 83 ], in contrast, consider that H. pylori does not have a lithogenic potential for the formation of cholesterol gallstones. Stathopoulos et al [ 84 ] suggest that H. pylori infection may affect gallbladder function, namely leading to a decrease in concentration ability.…”
Section: Helicobacter Pylori and Helimentioning
confidence: 99%
“…Cholecystectomy is the main treatment method for gallstones, but various complications exist. With the recognition of the importance of gallbladder function and the side effects of cholecystectomy, experts are increasingly advocating conservation of gallbladder function [3]. Procedures used in the past, such as percutaneous cholecystolithotomy, percutaneous cholecystostomy, extracorporeal shockwave lithotripsy, and dissolution therapy, have limitations, such as continued gallstone recurrence [4].…”
mentioning
confidence: 99%